2005
DOI: 10.1111/j.1582-4934.2005.tb00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator - activated receptor ? overexpression inhibits pro-fibrogenic activities of immortalised rat pancreatic stellate cells

Abstract: Pancreatic stellate cells (PSCs) play a key role in the development of pancreatic fibrosis, a constant feature of chronic pancreatitis and pancreatic cancer. In response to pro‐fibrogenic mediators, PSCs undergo an activation process that involves proliferation, enhanced production of extracellular matrix proteins and a phenotypic transition towards myofibroblasts. Ligands of the peroxisome proliferator‐activated receptor gamma (PPARγ), such as thiazolidinediones, are potent inhibitors of stellate cell activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Recent reports demonstrate that PPAR␥, a member of the nuclear receptor superfamily, acts as a repressor of type I collagen synthesis (16,17,33). Our data confirm that exogenously expressed PPAR␥ down-regulates collagen expression in a dose-responsive manner in human lung fibroblast cells as well as human aortic smooth muscle cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recent reports demonstrate that PPAR␥, a member of the nuclear receptor superfamily, acts as a repressor of type I collagen synthesis (16,17,33). Our data confirm that exogenously expressed PPAR␥ down-regulates collagen expression in a dose-responsive manner in human lung fibroblast cells as well as human aortic smooth muscle cells.…”
Section: Discussionsupporting
confidence: 78%
“…The thiazolidinedione compounds and certain prostaglan- dins have been used to demonstrate that activation of PPAR␥ inhibits collagen synthesis (18) and fibrosis in lung (14,15,19,57), kidney (8,9,58), liver (10,11,33,36,59), cardiac fibroblasts (60), and skin (61). The issue of endogenous ligand for PPAR␥ in cells has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF, and the PPARγ ligand PGJ 2 in a manner similar to that of their cultured primary cell counterparts (34)(35)(36). The combined use of cultured primary PaSCs and immortalized cells, coupled with the use of coculture systems (for example, coculture of acinar cells and PaSCs), is likely to provide additional mechanistic insights into the biology of PaSCs.…”
Section: Figurementioning
confidence: 99%
“…There are also several reports from in vitro experiments using PaSCs that show key roles in the activation and/or proliferation process for MAPK pathways, in particular, ERK1/2, p38 kinase, and JNK (50,52,53,66,109,110); PI3K and PKC (111); PPARγ (36,112); NADPH oxidases (our unpublished observations); and ethanol metabolism to acetaldehyde (18). In these studies, inhibition of most of these pathways results in attenuation of the activation and proliferation of PaSCs, but activation of PPARγ seems to block PaSC activation (36,112). It has also been reported that activated rat PaSCs express COX-2 when stimulated with TGF-β 1 and other cytokines (45), as well as when stimulated with conditioned media from human pancreatic tumor cells (113).…”
Section: Potential Treatments For Pasc Disordersmentioning
confidence: 99%
“…Because PSCs lose their adiopogenic properties upon activation, negative regulation of PPAR-c signaling is likely to be associated with PSCs activation. Studies using PPAR-c ligands and overexpression of PPAR-c have implicated this pathway in the maintenance of PSCs quiescence [37,38]. PPAR-c ligands inhibited proliferation, MCP-1 production, collagen synthesis, and a-SMA expression in PSCs [37].…”
Section: Ppar-cmentioning
confidence: 99%